Α‐Borylated Phosphorus Ylides (α‐BCPs): Electronic Frustration within a C−B π‐Bond Arising from the Competition for a Lone Pair of Electrons. Issue 59 (12th October 2018) - Radius, Michael; Breher, Frank
Abstract: The concept and the first example for electronic frustration within a C−B π‐bond arising from the competition for a lone pair of electrons is reported. The α‐borylated phosphorus ylide (α‐BCP) Ph3 PC(CH3 )BEt2 (1 ) has been synthesized, characterized, and investigated with the aid of density functional theory calculations. These show the presence of a highly polarized C−B π‐bond, induced by the electron‐withdrawing Ph3 P + substituent. This competition for the C‐based lone pair of electrons leads to an FLP‐type reactivity (FLP=frustrated Lewis pair), which has been demonstrated by reacting 1 with various small molecules: the dimeric insertion products [Ph3 PC(CH3 )COBEt2 ]2 (2 ) and [Ph3 PC(CH3 )(CO2 )BEt2 ]2 (5 ) result from the reaction of 1 with CO and CO2, respectively, whereas monomeric products of the general formula [Ph3 PC(CH3 )(XYZ)BEt2 ] were obtained by treating 1 with COS (3 ), CS2 (4 ) or the heterocumulenes PhNCO (6 ) and PhNCS (7 ). Abstract : A strained C−B π‐bond : The concept and the first example for electronic frustration within a C−B π‐bond arising from the competition for a lone pair of electrons is reported. The α‐borylated phosphorus ylide (α‐BCP) Ph3 PC(CH3 )BEt2 (1 ) has been synthesized, characterized, and investigated with the aid of density functional theory calculations. 1 has been demonstrated to react with various small molecules.